Peranan Perempuan Bugis dalam Penyebaran Islam di Alam Melayu: The Role of Bugis Women in The Spread of Islam in Malay World - Mohd Nasir, Nur Dina Najati; Mohd Nor, Mohd Roslan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2024)
This research attempts to explore the role of Bugis women in the spread of Islam in the Malay World. As a tribe with strong Islamic cultural roots in South Sulawesi, Bugis women have an important role in spreading these teachings in the surrounding region. Through family support, religious teaching, involvement in community activities, influence in politics and so on, Bugis women have played a significant role in shaping and strengthening Islamic identity in society in the Malay world. This study opens up the space to understand more about the role of women in the dynamics of the spread of Islam, as well as its impact on the social and cultural structure in the region. The conclusion of this research can provide a deeper insight into how Bugis women have become important agents in changing the religious and cultural landscape in the Malay World with the influence of Bugis-Makassar culture as well as the role of women in Islam which tends to dignify the high position of women in Islam . Keywords: Bugis women, spread of Islam, culture, Malay World